GAMBARAN GEJALA GANGGUAN SALURAN PERNAFASAN PADA POLISI LALU LINTAS DI WILAYAH KOTA JEMBER - Rofikoh, Hidayatul; Susanto, Gunawan (FKM - UNEJ, 2008)
Air Polution problem has became public health problems, especially in industrial countries where there are a lot of numbers of factories and motorcycles. Air pollution resulted from the motorcycle has a great impact for the police officers who work in those risky, dense and vital town street of accidents. Their job is a risky job for the effects of both acute and chronic air pollution symptoms.This research aims to identify the symptoms of respiratory tract disorders which affect the police officers in Jember.This research uses a descriptive method. The populations include all 137 police officers. The sample of the research is 34 respondents that is collected through quota sampling technic. The data is taken using a questioner from 6 to 10 June 2008.The result of the research shows that the acute symptom happens in 28 respondent (82, 4%), the chronic symptoms are experienced by 5 respondents (14, 7%), and the respondent who shows no symptoms is 1 responden (2,9%).Based on the finding, the researcher suggests that the police officers should aware of the importance of masker application in doing their job. Â Keywords : Respiratory tract disorder, Police Officer